Evaluating the alignment of the refugee status determination process with international and national human rights and refugee law: a cross-country analysis of Sweden and South Africa - Aytan, Selma (Department of Public Law, 2024)
In South Africa, the domestic refugee legislation, the Refugees Act 130 of 1998, was established in 1998.1 However, the country continues to struggle to correctly implement and apply the refugee law in a successful manner. Furthermore, outside its domestic refugee legislation, South Africa has both ratified and signed the 1951 United Nations Convention Relating to the Status of Refugees2 (1951 Convention) as well as the Organization of African Unity Convention Governing the Specific Aspects of Refugee Problems in Africa (OAU Refugee Convention).3 The country has hence committed to honoring the outlined obligations in both conventions in accordance with international law and to enact the Refugees Act.4 South Africa has further agreed to the 1967 Protocol Relating to the Status of Refugees5 and the 1948 United Nations Universal Declaration on Human Rights (UDHR).6 An important section that is outlined in all of these instruments is the right to seek and enjoy asylum. Further, the 1951 Convention was established to specifically protect people who are fleeing any form of persecution in their country of origin due to grounds such as race, religion, nationality, political opinion or membership to a particular social group.7 However, regardless of the provided grounds, South Africa has at times shown to fail to recognize such grounds during the refugee status determination process. With the country's extensive processing times as well as the hardship to receive more than a temporary residency in the country for long periods of times, many refugees and/or asylum seekers are put into uncertain circumstances which can have negative effects on both their physical and mental health. Sweden, a country on the opposite north altitude of South Africa, has traditionally had a wellestablished outwardly image of being an open and welcoming country for refugees. As a member-state of the European Union, Sweden is obliged to follow any policies that the EU develops. The European Council in 1999 began to develop the Common European Asylum System (CEAS)8, which would be foundational in the inclusive and full application of the 1951 Convention.9 This established system has undergone a couple of different developmental periods since its inception. During, what is commonly referred to as, the European influx of refugees that began in 2015, many deficiencies in the EU refugee and asylum policies and laws were exposed. Consequently, many of the member-states who were affected began to increase their engagement in terms of the future direction of the EU asylum and refugee policies and laws. Numerous countries additionally began to refuse their obligations in terms of EU policies and laws surrounding the topic. The European refugee influx also marked an important transition in Sweden's refugee and asylum policies. Prior to 2015, Sweden took pride in being a generous state in terms of their national asylum and refugee system, as well as the quality of care which refugees and asylum seekers were provided at the point of arrival. One prime example of this was in 2013 when all Syrian and stateless persons seeking asylum were guaranteed and provided permanent residency, given that they were arriving from war-torn Syria. This policy has since changed, and it is far more complicated and difficult for an asylum seeker and refugee to attain permanent residency. There has been a notable switch in Sweden's stance on accepting and receiving refugees and asylum seekers even after the 2022 election, in which a far-right majority now is politically in charge of the country. With the difficulties that asylum seekers and refugees are now facing in terms of having their refugee status determined globally, this paper seeks to first, investigate whether South Africa's refugee status determination process has ever fully been aligned with human rights and refugee law; secondly, investigate why Sweden has begun to move towards a similarly difficult refugee status determination process as South Africa. The analysis will be conducted through desk-top research comprising academic literature, international and regional treaties, legislation, government reports, policy documents, relevant case studies, academic publications, journal articles, book chapters and books. By applying desk-top research, the dissertation will attempt to provide a comprehensive understanding of the challenges and difficulties that refugees and asylum seekers face today in both countries.